Islamisasi Konsep Etika Politik Niccolo Machiavelli: Islamization of Niccolo Machiavelli's Concept of Political Ethics - Abdul Wahid; Anisa Aliya; Neng Eri Sofiana; Fatimatuz Zahra (University of Darussalam Gontor, Indonesia, 2023)
Politics is known as an activity that is synonymous with negative and 'evil' things, as well as in The Prince, Niccolo Machiavelli describes politics with the impression of putting aside morals, even to conquer a territory or advance to become a leader, it can be through cunning ways, vile, and evil. This paper will discuss the Islamization of Niccolo Machiavelli's political ethics by using the concept of Islamization promoted by Syed Naquib al-Attas, and the concept of political in Islam. It is carried out by library research which in collecting data relies on data from the literature. As for the result, in Islamic political ethics, religious values must color the behavior of power holders. Al-Qur'an as a source of ethical values, if applied in power will produce a government with high moral values, so as to be able to realize happiness and justice equally for the community.